Do dietary supplements prevent loss of muscle mass and strength during muscle disuse? A systematic review and meta-analysis of randomized controlled trials - Ye, Hua; Yang, Jia-Ming; Luo, Yun; Long, Yi; Zhang, Jia-Hong; Zhong, Yan-Biao; Gao, Feng; Wang, Mao-Yuan (Frontiers in Nutrition, 2023)
Objective: We performed a systematic review and meta-analysis of existing randomized controlled trials (RCTs) to assess whether dietary supplements can prevent loss of muscle mass and strength during muscle disuse. Methods: We searched the following databases: PubMed, Embase, Cochrane, Scopus, Web of Science, and CINAHL for RCTs assessing the effect of dietary supplements on disuse muscular atrophy without language and time restrictions. Muscle strength and leg lean mass were used as the main outcome indicators. Muscle cross-sectional area (CSA), muscle fiber type distribution, peak aerobic capacity and muscle volume were used as secondary outcome indicators. The risk of bias was assessed using the Cochrane Collaboration's Risk of Bias tool. Heterogeneity was tested using the I2 statistic index. Mean and standard deviation of outcome indicators were extracted from the intervention and control groups to calculate effect sizes and 95% confidence intervals, with the significance level set at P<0.05. Results: Twenty-one RCTs were included with a total of 349 subjects. The results showed that dietary supplements had no effect on muscle strength, CSA, peak aerobic capacity or muscle volume. But dietary supplements have a protective effect on the lean mass of the legs. Conclusion: Dietary supplements can improve lean leg mass, but did not show a tendency to have an effect on muscle strength, CSA, peak aerobic capacity or muscle volume during muscle disuse.